Carnival, combat and hierarchy among the supporters that form a «barra brava» in Bogotá - Castro Lozano, John (2020)
The article tries to understand the carnival and the combat between the supporters who form a «barra brava» in Bogotá, expressions and behaviors that constitute internal order and hierarchy. In this aspect, the ethnographic fieldwork was carried out from the first semester of 2017 to the first semester of 2018, with supporters of «Millonarios Fútbol Club» who form Blue Rain. Ethnographic fieldwork makes it possible to «be there» with the subjects and the social group to describe and participate in the different practices in which they intervene. In this way, the article is organized as follows: first, the introduction, which allows contextualizing the research problem; second, the research methodology and approach; third, the participation in the festivity and permanence in fights, demonstrate the «aguante»; and fourth, the socialization processes and the constitution of the hierarchy. Finally, some conclusions are exposed.